Towards an essential humanistic conception of social institutions: state of the art - Liliana Beatriz Irizar (Civilizar, 2008)
The initial review of the literature for this study allowed us to ecognize four different philosophical approaches that support the same amount of sociological paradigms. Such paradigms are concurrently present in other human sciences that deal with the topic of social institutions in one way or another. Therefore, after analyzing the topos of the notion institution, and with the intention of distinguishing this notion, we synthetically analyze the conceptualizations of institution as proposed by the following approaches: empirical-positivist, critical-dialectic, hermeneutical-existential, and metaphysical-realistic.